TRICHOPHYTON INTERDIGITALE CAUSING SEVERE TINEA CORPORIS AND TINEA CRURIS ET CORPORIS - Seeba Hussain (Student's Journal of Health Research, 2023)
Background: For many years, India has been plagued by an epidemic-like scenario of chronic, extensive, and resistant dermatophytosis. Dermatophytosis, also known as tinea, was once regarded as a minor infection that was simple to treat. Without oral antifungal agents, the use of such topical preparations to treat dermatophytosis can result in extensive lesions and fungal resistance. This study aimed to determine the aetiology and dermatophyte species associated with tinea corporis and tinea cruris et corporis with extensive lesions. Methods: The Department of Dermatology at the tertiary care centre conducted a study for two years. The consent of 158 patients was obtained. All patients with clinical findings of tinea corporis and tinea cruris et corporis who tested positive for KOH and/or culture were enrolled in the study. A thorough history was obtained. Findings: Results indicated that 149 (94.30%) were KOH positive and 158 (100%) were culture positive. Only Trichophyton interdigitale was isolated from 158 patients. None of the patients tested positive for HIV, and six patients (4%) had diabetes. Seventy percent of the patients reported using antifungal, antibiotic, and topical steroid creams in various combinations, and nearly ten percent used corticosteroid creams alone. Rest was unaware of the name of the moisturiser they used. Conclusion: Local immunity is lowered by topical steroids, which contribute to the development of extensive and atypical lesions. Dermatomycosis has reached epidemic proportions in this Katihar region. This region is rife with the misuse of unregulated steroid mixtures.